Low-temperature sintering of silicon carbide membrane supports from disks to single- and 19-channel tubes. Issue 6 (June 2022) - Zhou, Jian; Gu, Qilin; Liu, Feng; Feng, Shasha; Zhong, Zhaoxiang; Xing, Weihong
Abstract: As the configuration of asymmetric ceramic membranes is determined by the membrane supports, a low temperature sintering process was developed to prepare ceramic membrane supports from disks to single- and 19-channel tubes. The residual of NaA zeolite was introduced into the silicon carbide (SiC) matrix, and porous SiC membrane supports were successfully prepared at 1100 °C. Compared with the disk-like support, the open porosity, average pore size and pure water permeance of the single-channel supports obviously increased, and their bending strength decreased accordingly. These differences were mainly attributed to the incorporation of organic plasticizer and the change in molding process. Notably, the pure water permeance of disks, single- and 19-channel tubes was 70 ± 3, 74 ± 4 and 22 ± 1 m 3 ·m −2 ·h −1 ·bar −1, respectively, which was much higher than the previously reported values. Therefore, this work provides important guides to develop of new generation ceramic membranes for practical application.